Management of Metastatic Endometrial Cancer: Physicians’ Choices Beyond the First Line. A MITO Survey - Giannone, Gaia; Castaldo, Daniele; Tuninetti, Valentina; Scotto, Giulia; Turinetto, Margherita; Valsecchi, Anna Amela; Bartoletti, Michele; Mammoliti, Serafina; Artioli, Grazia; Mangili, Giorgia; Salutari, Vanda; Lorusso, Domenica; et al. (Frontiers in Oncology, 2022)
Background Endometrial cancer (EC) therapeutic and diagnostic approaches have been changed by the development of a new prognostic molecular classification, the introduction of dostarlimab in microsatellite instability (MSI) high pre-treated advanced EC patients with further expected innovation deriving from lenvatinib plus pembrolizumab regardless MSI status. How this is and will be translated and embedded in the clinical setting in Italy is not known; this is why we developed Multicentre Italian Trials in Ovarian cancer and gynaecologic malignancies (MITO) survey on the current practice and expected future changes in EC. Methods We designed a self-administered, multiple-choice online questionnaire available only for MITO members for one month, starting in April 2021. Results 75.6% of the respondents were oncologists with a specific focus on gynaecologic malignancies and 73.3% of the respondents declared the availability of clinical trials in second line treatment for advanced EC. The therapeutic algorithm in second line was heterogeneous, being the most frequent choice administering anthracyclines followed by endocrine therapy or enrolling in clinical trials. While more than half of the clinicians declared that they performed the molecular classification, only six/45 respondents (13.3%) ran all the tests needed for it. On the other hand, 80% of them declared regular assessment of MSI status with IHC as recommended. The therapeutic approach in MSI high advanced EC patients has changed since dostarlimab approval. Indeed the most frequent choice in second line has been chemotherapy (53.3%) before its availability, while dostarlimab has been preferred in more than three-fourths of the cases (75.6%) after its approval. As for MSS patients, 77.8% of clinicians would choose lenvatinib plus pembrolizumab for them in second line once approved. Conclusions Despite the selected sample of respondents from Italian MITO centres showing good knowledge of diagnostic and therapeutic innovations in EC, these are not fully implemented in everyday clinics, except for MSI status assessment.